Nowoczesne technologie wspomagające funkcjonowanie osób z niepełnosprawnością w doświadczeniach Ośrodka Wsparcia i Testów w Sosnowcu = Modern technologies supporting the functioning of people with disabilities in the experiences of the Support and Testing Center in Sosnowiec - Wolny, Jakub; Flanczewska-Wolny, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
There are many factors that generate the risk of marginalization for people with disabilities. However, in the authors` opinion, one of the most significant is the limited accessibility in the broad sense, both physically, in the form of architectural barriers, and mentally, in the persistent social stereotypes about their abilities.
Keywords: niepełnosprawność; technologie asystujące i wspomagające; disability; assistive and supportive technologies